Estudio de factibilidad para la implementación de una marisquería en la parroquia El Carmen cantón La Mana, provincia de Cotopaxi. - Villacres Gomez, Eugenia Marisol (2012)
The main purpose of this research is focused on a Feasibility Study for the Implementation of the Parish Seafood in Canton La Maná Carmen. This study originated after analyzing the market and discovers the lack of seafood restaurants that provide good service to users in the field above. In addition to analyzing the benefits of the users such as purchasing power and high acceptance for seafood. These primary factors contributed to initiate a feasibility study to allow the researcher to know the probability of negative or positive implement a seafood restaurant in El Carmen. For the development of this study applied various strategies and techniques that allow to improve the clarity Market research, technical study and financial Economic Survey. Finally in the conclusion from the financial point of view we could say that the project is viable, showing a total investment of average which indicates that the business is highly profitable.